Haemorrhagic toxin and lethal toxin from Clostridium sordellii strain vpi9048: molecular characterization and comparative analysis of substrate specificity of the large clostridial glucosylating toxins. (4th August 2014) - Genth, Harald; Pauillac, Serge; Schelle, Ilona; Bouvet, Philippe; Bouchier, Christiane; Varela‐Chavez, Carolina; Just, Ingo; Popoff, Michel R.
Summary Large clostridial glucosylating toxins (LCGTs) are produced by toxigenic strains of Clostridium difficile, Clostridium perfringens, Clostridium novyi and Clostridium sordellii. While most C. sordellii strains solely produce lethal toxin (TcsL), C. sordellii strain VPI9048 co‐produces both hemorrhagic toxin (TcsH) and TcsL. Here, the sequences of TcsH‐9048 and TcsL‐9048 are provided, showing that both toxins retain conserved LCGT features and that TcsL and TcsH are highly related to Toxin A (TcdA) and Toxin B (TcdB) from C. difficile strain VPI10463. The substrate profile of the toxins was investigated with recombinant LCGT transferase domains (rN) and a wide panel of small GTPases. rN‐TcsH‐9048 and rN‐TcdA‐10463 glucosylated preferably Rho‐GTPases but also Ras‐GTPases to some extent. In this respect, rN‐TcsH‐9048 and rN‐TcdA‐10463 differ from the respective full‐length TcsH‐9048 and TcdA‐10463, which exclusively glucosylate Rho‐GTPases. rN‐TcsL‐9048 and full length TcsL‐9048 glucosylate both Rho‐ and Ras‐GTPases, whereas rN‐TcdB‐10463 and full length TcdB‐10463 exclusively glucosylate Rho‐GTPases. Vero cells treated with full length TcsH‐9048 or TcdA‐10463 also showed glucosylation of Ras, albeit to a lower extent than of Rho‐GTPases. Thus, in vitro analysis of substrate spectra using recombinant transferase domains corresponding to the auto‐proteolytically cleaved domains, predicts more precisely the in vivo substrates than the full length toxins. Except for TcdB‐1470, all LCGTs evoked increased expression of the small GTPase RhoB, which exhibited cytoprotective activity in cells treated with TcsL isoforms, but pro‐apoptotic activity in cells treated with TcdA, TcdB, and TcsH. All LCGTs induced a rapid dephosphorylation of pY118‐paxillin and of pS144/141‐PAK1/2 prior to actin filament depolymerization indicating that disassembly of focal adhesions is an early event leading to the disorganization of the actin cytoskeleton.